2010
DOI: 10.1007/s11665-010-9756-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Distortion and Warpage of 7249 Aluminum Alloy After Quenching and Machining

Abstract: The objective of this study is to determine the effect of solution treatment temperature, quenching media, and various machining sequences on the warpage behavior of aluminum 7249 alloy aged to T6 and T7¢ tempers. Large extrusions of 7249 aluminum alloy with fins were cut into 108 ''T'' sections. The samples were solution-treated, aged, and machined. Three solution temperatures (445, 474, and 505°C), two quenching media (water and 20% polyalkylene glycol), two aging treatments (T6 and T7¢), and three machine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Further, they showed, machining induced residual stresses as main cause for distortion for workpieces machined below 5-6 mm thickness and quenching stresses are responsible for workpieces greater than 10 mm thick. Keleshian et al, [24] performed heat treatment and machining experiments on aluminium alloy 7249 and concluded that water quenching and peak aged components give more warpage. Ye et al, [25] concluded that more fluctuant residual stress distribution was found at the final path of milling on aeronautical monolithic components.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they showed, machining induced residual stresses as main cause for distortion for workpieces machined below 5-6 mm thickness and quenching stresses are responsible for workpieces greater than 10 mm thick. Keleshian et al, [24] performed heat treatment and machining experiments on aluminium alloy 7249 and concluded that water quenching and peak aged components give more warpage. Ye et al, [25] concluded that more fluctuant residual stress distribution was found at the final path of milling on aeronautical monolithic components.…”
Section: Introductionmentioning
confidence: 99%
“…Depth of cut and width of cut were found to be significant contributors in machining distortion [12]. Keleshian, N, et al, in their work conducted machining experiments on aluminium alloy 7249 and observed that solution treatment temperature, quenching media, and various machining sequences affect distortion [13]. Chatelain, Jean-François, Jean-François Lalonde, and Antoine S. Tahan conducted experiments on a thin representative part to compare distortions with and without existing residual stresses in work pieces and concluded that initial residual stresses embedded within raw material has an effect on the final part deformation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nesta fase, não há praticamente influência de tensões residuais na microestrutura que seriam capazes de causar algum tipo de distorção (Keleshian et al, 2011).…”
Section: ____________________________________________________________unclassified